2007
DOI: 10.1152/ajpheart.01296.2006
|View full text |Cite
|
Sign up to set email alerts
|

The role of the renin-angiotensin system and oxidative stress in spontaneously hypertensive rat mesenteric collateral growth impairment

Abstract: Recent clinical and animal studies have shown that collateral artery growth is impaired in the presence of vascular risk factors, including hypertension. Available evidence suggests that angiotensin-converting enzyme inhibitors (ACEI) promote collateral growth in both hypertensive humans and animals; however, the specific mechanisms are not established. This study evaluated the hypothesis that collateral growth impairment in hypertension is mediated by excess superoxide produced by NAD(P)H oxidase in response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
44
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 78 publications
7
44
0
Order By: Relevance
“…In agreement with our results demonstrating a beneficial effect of reduction in oxidative stress in JCR animals, Miller et al (22) demonstrated that mesenteric collateral growth, impaired in SHRs, was significantly improved by apocynin. Since a common characteristic of the JCR (29) and SHR (22) phenotype is elevated oxidative stress, these results indicate that lowering oxidative stress in phenotypes where it is elevated is critical for the restoration of collateral growth.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with our results demonstrating a beneficial effect of reduction in oxidative stress in JCR animals, Miller et al (22) demonstrated that mesenteric collateral growth, impaired in SHRs, was significantly improved by apocynin. Since a common characteristic of the JCR (29) and SHR (22) phenotype is elevated oxidative stress, these results indicate that lowering oxidative stress in phenotypes where it is elevated is critical for the restoration of collateral growth.…”
Section: Discussionsupporting
confidence: 93%
“…However, angiotensin II type 1 receptor (AT 1 R) blockade significantly restored CCG in JCR animals, which was associated with a significant reduction in myocardial O 2 Ϫ ⅐ levels (29). Decreasing ROS improved mesenteric collateral development in a rat model of spontaneous hypertension [the sponteneously hypertensive rat (SHR)] (22).…”
mentioning
confidence: 99%
“…But we also believe that this model serves as a general model for collateral growth. In support of this are studies that show a similar impairment in collateral growth in both the hindlimb and mesentery of SHRs (10,27). In addition, we have observed similar histological results including a well-defined intima with increased endothelial cell density in vessels we have identified as primary collaterals in the hindlimbs of mice, rats, and pigs (unpublished observations).…”
supporting
confidence: 87%
“…Collateral growth occurs in a variety of organ systems and vascular beds, including the heart (23,114,115), hindlimb (11,12), mesentery (69), and the brain (11). In the rat heart, the response is extraordinary, with substantial increases in collateral growth in as little as 10 days (Fig.…”
Section: General Concepts In the Initiation Of Collateral Growthmentioning
confidence: 99%